Madame Bovary ? elle habitait là-bas... - Ida Merello (Flaubert: Revue Critique et Génétique)
After the publication of Madame Bovary, investigations began to find the models of Flaubert's characters and the true locations of the story. This type of criticism continues: for example, recently Daniel Fauvel has just discovered another “Delamare case”. My article gives reviews the readings of Madame Bovary, especially in Normandy, since the publication of the work until now, to show how the links have been forged between Flaubert's life (and the people he known) and the characters of his book, to the point of creating real intrigues, which also bring into play the name of Bovary to find a number of explanations in relation to the knowledge, both familiar, of the writer. Echoes therefore seem to leave the novel to return to it, enriched with a host of small details that try to penetrate into the biography of the author. It's another way of doing criticism, to manage to grasp what triggered the imagination. Among these diggers of the soil, Georgette Leblanc-Maeterlinck seeks to gain her little notoriety at the beginning of the 20th century, by superimposing Emma on Delphine Delamare, as if Flaubert had only wanted to paint the portrait of the latter, and by finding in her good the character of Felicity. What characterizes Georgette Leblanc-Maeterlinck's little book, from creating an illusion of authenticity of places and people, to presenting their photographs, is a somewhat mannered attitude of feminine solidarity with Emma, in the name of the new women’s freedoms of which she herself was proud.